Simulating Family Life Courses: An Application for Italy, Great Britain, and Scandinavia - Maria Winkler-Dworak; Éva Beaujouan; Paola Di Giulio; Martin Spielauer (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
Family patterns in Western countries have substantially changed across the 1940 to 1990 birth cohorts. Adults born more recently enter more often unmarried cohabitations and marry later, if at all. They have children later and fewer of them; births take place in a non-marital union more often and, due to the declining stability of couple relationships, in more than one partnership. These changes have led to an increasing diversity in family life courses. In this paper, we present a microsimulation model of family life trajectories, which models the changing family patterns taking into account the complex interrelationships between childbearing and partnership processes. The microsimulation model is parameterized to retrospective data for women born since 1940 in Italy, Great Britain and two Nordic countries (Norway and Sweden), representing three significantly different cultural and institutional contexts of partnering and childbearing in Europe. Validation of the simulated family life courses against their real-world equivalents shows that the simulations not only closely replicate observed childbearing and partnership processes, but also give good predictions when compared to more recent fertility indicators. We conclude that the presented microsimulation model is suitable for exploring changing family dynamics and outline potential research questions and further applications.
Keywords: 300; Family life course; fertility; partnerships; microsimulation; Italy; Great Britain; Norway; Sweden